بين الخطاب الأدبي و الخطاب الفلسفي - بحث في الخصوصية - حمراوي, خضرة (Revues faculté des lettres et des langues, 2018)
Abstract: Discourse has several types that are different in structure, nature, aims and study methods. This is the main interest of discourse theories aiming at naturalizing discourses. Research in the literary discourse and philosophical discourse specificity, and the detection of the similarities and differences between them may be considered as one of the main issues and the complex entrances.Therefore, we will focus on the specificity of each discourse in form and content; the language and style ,the producer and the receiver of the discourse, as well as the role that seeks to achieve it according to a method that can balance between them. الملخص          للخطاب أنواع عدَّة تتمايز في بنائها وطبيعتها وأهدافها ومناهج  دراستها، وهذا ما تهتم به نظريات الخطاب التي تعمد إلى تجنيس الخطابات .و لعل البحث في خصوصية الخطاب الأدبي و الخطاب الفلسفي والكشف عن أوجه التشابه والاختلاف بينهما من القضايا المهمة والمتشعبة المداخل. لذلك سنقف عند خصوصية كل منهما شكلا ومضمونا، لغة و أسلوبا، عند منتج الخطاب و متلقيه، و الدور الذي يروم إلى تحقيقه وفق منهج يوازن بينهما .